Answer:
try 1.5 or 0.6 repeating
Step-by-step explanation:
hope this helps
Step-by-step explanation:
d = √(x2 - x1)^2 + (y2 - y1)^2 + (z2 - z1)^2
P1(0, 0, 0) P2(-6, 8, 3)
Substitute the values in the above equation and you will get
d = √(-6 - 0)^2 + (8 - 0)^2 + (3 - 0)^2
= √(36 + 64 + 9)
= √109
= 10.44
The values are equal.
Root 5.76= 2.4
-2.4=-2.4
Answer:
k = 168
Step-by-step explanation:
rewrite the equation
Multiply 42 to isolate k. Do the same on the other side
42 * 4 = 168 When you do that you get 168.